2020
DOI: 10.1080/19420862.2020.1715705
|View full text |Cite
|
Sign up to set email alerts
|

Improved translation of stability for conjugated antibodies using an in vitro whole blood assay

Abstract: For antibody-drug conjugates to be efficacious and safe, they must be stable in circulation to carry the payload to the site of the targeted cell. Several components of a drug-conjugated antibody are known to influence stability: 1) the site of drug attachment on the antibody, 2) the linker used to attach the payload to the antibody, and 3) the payload itself. In order to support the design and optimization of a high volume of drug conjugates and avoid unstable conjugates prior to testing in animal models, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Conjugate CLL1– 9d also exhibited excellent stability properties when exposed to whole blood from various species for 24 h (Table S5). These results suggested that the conjugate and other ADCs derived from the 9d pyrophosphate-containing linker-drug would display favorable stability outcomes if/when assessed in in vivo settings . Accordingly, we continued our exploration of the BRD4 degraders described in this work in an effort to identify additional biologically active ADCs that could be considered for in vivo efficacy assessments.…”
Section: Resultsmentioning
confidence: 81%
“…Conjugate CLL1– 9d also exhibited excellent stability properties when exposed to whole blood from various species for 24 h (Table S5). These results suggested that the conjugate and other ADCs derived from the 9d pyrophosphate-containing linker-drug would display favorable stability outcomes if/when assessed in in vivo settings . Accordingly, we continued our exploration of the BRD4 degraders described in this work in an effort to identify additional biologically active ADCs that could be considered for in vivo efficacy assessments.…”
Section: Resultsmentioning
confidence: 81%
“…In addition, and in agreement with our previous studies, a second control DAR6 conjugate related to STEAP1– 3a -D6 (HER2– 3a -D6; see Figure S1c for evidence of low HER2 expression in PC3-S1 cells) exhibited excellent in vitro stability properties in independent experiments conducted using whole blood from mice, rats, cynomolgus monkeys, and humans (Table S2). These data suggested that conjugates such as STEAP1– 3a -D6 were likely to exhibit acceptable in vivo stability properties in the various species since our previous ADC studies established (1) a reasonable in vitro to in vivo correlation, and (2) the antigen recognized by a given conjugate did not significantly impact the whole-blood stability outcomes . As a result of the above findings, we focused our subsequent efforts on DAR6 ADCs derived from the engineered LC-K149, HC-L174, and HC-Y373 triple mutant STEAP1 monoclonal antibody.…”
Section: Resultsmentioning
confidence: 92%
“…Several considerations should be factored in, particularly for matrix incubations in ex vivo studies. For example, there may be differences in blood, serum, or plasma incubations or the translation from animal to human matrices . Furthermore, it may be necessary to study injection site stability .…”
Section: Applications Of the Methodsmentioning
confidence: 99%